AI-Augmented Creativity in Airline Crisis Management: Balancing Novelty and Strategic Feasibility - MoghadasNian, SeyyedAbdolHojjat (12th National Interdisciplinary Research Conference in Management & Humanistic Sciences, 2025)
This study investigates the integration of generative AI into airline crisis management, with a primary focus on how AI-augmented creativity can be harnessed to generate practically viable recovery solutions. The research addresses the critical balance between creative novelty and strategic feasibility, aiming to delineate effective human–AI team compositions as well as communication strategies that enhance passenger trust during operational disruptions. A mixed-methods approach was utilized, combining quantitative data from controlled experiments and simulation studies with qualitative insights gathered through semi-structured interviews and document analysis. Findings reveal that while human-AI collaborations tend to yield outputs with lower raw novelty, these solutions demonstrate substantially higher financial, environmental, and operational value than human-only outputs. Moreover, evidence indicates that mixed teams achieving an optimal human-to-AI ratio and leveraging diverse expertise significantly improve decision-making and situational responsiveness. Transparent and empathetic communication emerges as vital to restoring and maintaining passenger trust in AI-driven responses. The study contributes to digital transformation and human–AI collaboration theories, offering actionable recommendations for airline managers and policymakers to optimize crisis management protocols. In particular, strategic investments in training, robust KPI dashboards, and phased AI deployments are advised to foster both innovation and long-term operational excellence.